Concrete block structural masonry beam shear design: theoretical and experimental analysis and recommendations to the brazilian standards - Pasquantonio, R. D.; Parsekian, G. A.; Camacho, J. S. (IBRACON - Instituto Brasileiro do Concreto, 2019)
Abstract Beams are subject a flexure and shear, with the last as the theme of this research. The purpose of this paper is to analyze specifications for the shear design of concrete block structural masonry beams, based on an extensive literature review and experimental tests here reported. From this scope, specifications for revision of Brazilian standardization are suggested. In the theoretical part, literature review from both national and international researchers were considered and the specifications of Brazilian standards, in addition to North American, Australian, Canadian and European, ABNT NBR 15961-1/2011, ABNT NBR 6118/2014TMS 402/2016, AS3700/2001, CSA S304/2014 and EuroCode6.1/2001, respectively. To analyze and validate the specifications of the literature, an experimental program was carried out assessing ten concrete block masonry beams results tested mainly to shear loads. Two-course high beams with three vertical load positions (position a/d) and two transverse reinforcement rates were tested. The specifications from the Brazilian and European standards led to considerably higher results than the experimental results, while those presented in the standards TMS 402/2016, AS3700/2001, CSA S304/2014 and NBR6118/2014 lead to results close to those obtained experimentally. As a conclusion, it can be noted that the rupture pattern is similar to that expected for reinforced concrete beams, the cracks were conditioned by the position of the loading point and by the mortar joints positions, the increase in the transverse reinforcement ratio led to an increase in the shear force. Results indicate that the consideration of apparent increase in shear strength by the ratio M ⁄ (V∙d) is not consistent. Eliminating this recommendation, considering the masonry shear strength equal to 0.35 MPa, limiting the stirrups tension to 0.90 of fyk and considering the contribution of the longitudinal reinforcement, it was possible to estimate the shear value at the rupture of each beam between 73% to 106% of the values verified in the tests.

Resumo Vigas são submetidas à flexão e cisalhamento, sendo esse último esforço o tema desta pesquisa. O objetivo deste trabalho é analisar especificações para dimensionamento ao esforço cortante de vigas de alvenaria estrutural em blocos de concreto, a partir de extensa avaliação da literatura e de ensaios experimentais aqui relatados. A partir desse escopo, são sugeridas especificações para revisão da normalização brasileira. Na parte teórica, foram considerados trabalhos anteriores tanto nacionais quanto internacionais e as prescrições das normas brasileiras NBR15691-1/2011 e NBR 6118/2014, além da norte-americana, australiana, canadense e europeia, TMS 402/2016, AS3700/2001, CSA S304/2014 e EuroCode 6.1/2001, respectivamente. Com intuito de analisar e validar as especificações da literatura foi realizado um programa experimental de análise de dez vigas de alvenaria com blocos de concreto submetidos principalmente ao esforço cortante. Foram consideradas vigas de duas fiadas, três posições da carga vertical, variando a/d, e duas taxas de armadura transversal. Na análise dos ensaios verificaram-se semelhanças no comportamento último das vigas de alvenaria armada com a teoria proveniente das vigas de concreto armado, com algumas particularidades de fissuração na região das juntas de argamassa. Além disso, as especificações estabelecidas pela norma brasileira e europeia levaram a resultados consideravelmente maiores do que os resultados experimentais, enquanto que os presentes nas normas TMS 402/2016, AS3700/2001, CSA S304/2014 e NBR6118/2014 levam a resultados próximos aos obtidos experimentalmente. Como conclusão pode-se destacar que o padrão de ruptura é semelhante ao esperado para vigas de concreto armado, as fissuras foram condicionadas pela posição do ponto de aplicação do carregamento e pelas juntas de argamassa, o aumento da taxa de armadura transversal levou ao aumento da força cortante de ruptura. Os resultados indicam não ser consistente a consideração de aumento aparente da resistência ao cisalhamento pela relação M ⁄ (V∙d). Eliminando-se essa recomendação, considerando a resistência da alvenaria igual a 0,35 Mpa, limitando a tensão nos estribos a 0,90 de fyk e considerando a contribuição da armadura longitudinal, foi possível estimar o valor de cortante na ruptura de cada viga entre 73% a 106% dos valores verificados nos ensaios.
Dimensionamento de vigas de alvenaria estrutural de blocos de concreto ao esforço cortante: análise teórica e experimental e recomendações à normalização brasileira
Keywords: beam; masonry; reinforced masonry; shear; viga; alvenaria; alvenaria armada; cisalhamento